Study protocol for the international Systemic Lupus Erythematosus Prospective Observational Cohort Study (SPOCS): understanding lupus and the role of type I interferon gene signature - Raj Tummala; Anna Berglind; Xia Wang; Henk Nab; Barnabas Desta; Edward R Hammond; Farhat Syed (BMJ Open)
Introduction The Systemic Lupus Erythematosus (SLE) Prospective Observational Cohort Study (SPOCS) aims to describe the disease course of SLE and its association with type I interferon gene signature (IFNGS) status.Methods and analysis SPOCS is an international, multicentre, prospective, observational cohort study designed to follow patients through biannual study visits during a 3-year observation period. Patients ≥18 years old with a physician diagnosis that meets the American College of Rheumatology or Systemic Lupus International Collaborating Clinics SLE classification criteria will be included. SPOCS will comprehensively analyse clinical features, disease progression and treatment, SLE outcomes, health status assessments and quality of life, and healthcare resource utilisation of patients with moderate to severe SLE. A four-gene test will be used to measure IFNGS status; scores will be compared with a pre-established cut-off. Patients will be stratified by low or high IFNGS expression levels. Enrolment began in June 2017, and study completion is expected in 2022. The total number of anticipated patients was initially planned for 1500 patients and was amended to 900 patients owing to slow accrual of eligible patients.Ethics and dissemination The ethics committee/institutional review board/independent ethics committee at each study site approved the SPOCS protocol prior to study initiation (protocol number: D3461R00001, version 3.0, 26 June 2019). Study findings will be disseminated through peer-reviewed publications and presentations at scientific meetings.Trial registration number NCT03189875.